The Public Sphere and the Internet in Latin America - Saavedra Utman, Jorge; Santos, Marcelo (Javnost-The Public, 2024)
To what extent does the notion of the public sphere serve to assess Latin America in networked times? The debate over the modern condition of the region and the contradictions of enlightenment values shaping a land conquered by the sword provides the backdrop for evaluating the pertinence of Habermas’s The Structural Transformation of the Public Sphere in the region, specifically regarding the chances the subaltern has to speak. Acknowledging its modern imprint and the varied criticisms it has received, the notion of the public sphere a la Habermas, offers a set of criteria for assessing the processes and outcomes of media and public communication development in Latin America. In this sense, this article connects the colonial imprint of Latin American nations, its struggles over media power, the meaning of communication, and the arrival of the Internet and Web 2.0 in the region through the notion of the public sphere. This overview exposes the features of the Internet in Latin America that perpetuate inequality, injustice, and the lack of voice while raising questions about the actual life of the “public” as a concept in the region.